Comparative analysis of prevalence of apical periodontitis in smokers and non-smokers using cone-beam computed tomography - Hanan A. Balto; Lama Alabdulaaly; Shaima Bahammam; Asma'a A. Al-Ekrish (Saudi Dental Journal)
Objective: The aim of this study was to compare the prevalence and size of periapical lesions among smokers and non-smokers using cone-beam computed tomography (CBCT). Materials and methods: Retrievable CBCT datasets for 46 male patients ≥18 years during a consecutive period from 2008 to 2016 were examined. The medical, smoking history and other clinical findings (signs of previous dental trauma; Decayed Missing Filled Teeth (DMFT) scores; the percentage of root filled teeth; and oral hygiene status) were obtained. Periapical status of all included teeth was assessed by CBCT images. Statistical analysis was conducted using t-test, Pearson correlation and multiple regression. Results: The prevalence of apical periodontitis was 13.93% in smokers and 14.26% in non-smokers with no significant difference (p = 0.936). The mean of the average size of lesions between the two groups were almost comparable, 3.50 mm in smokers and 2.89 mm in non-smokers (p = 0.567). Pearson correlation and multiple regression analysis showed that the percentage of lesion present and the average lesion size were not correlated to any independent variable. Conclusions: While smoking is considered a risk factor for marginal periodontitis, there was no difference between smokers and non-smokers in terms of apical periodontitis. Keywords: Apical periodontitis, CBCT, Prevalence, Smoking